Regulation by Nrf2 of IL-1β-induced inflammatory and oxidative response in VSMC and its relationship with TLR4 - González-Carnicero, Zoe; Hernanz, Raquel; Martínez-Casales, Marta; Barrús, María Teresa; Martín, Ángela; Alonso, María Jesús (Frontiers in Pharmacology, 2023)
Introduction: Vascular oxidative stress and inflammation play an important role in the pathogenesis of cardiovascular diseases (CVDs). The proinflammatory cytokine Interleukin-1β (IL-1β) participates in the vascular inflammatory and oxidative responses and influences vascular smooth muscle cells (VSMC) phenotype and function, as well as vascular remodelling in cardiovascular diseases. The Toll-like receptor 4 (TLR4) is also involved in the inflammatory response in cardiovascular diseases. A relationship between Interleukin-1β and Toll-like receptor 4 pathway has been described, although the exact mechanism of this interaction remains still unknown. Moreover, the oxidative stress sensitive transcription factor nuclear factor-erythroid 2-related factor 2 (Nrf2) promotes the transcription of several antioxidant and anti-inflammatory genes. Nuclear factor-erythroid 2-related factor 2 activators have shown to possess beneficial effects in cardiovascular diseases in which oxidative stress and inflammation are involved, such as hypertension and atherosclerosis; however, the molecular mechanisms are not fully understood. Here, we analysed the role of Toll-like receptor 4 in the oxidative and inflammatory effects of Interleukin-1β as well as whether nuclear factor-erythroid 2-related factor 2 activation contributes to vascular alterations by modulating these effects. Materials: For this purpose, vascular smooth muscle cells and mice aortic segments stimulated with Interleukin-1β were used. Results: Interleukin-1β induces MyD88 expression while the Toll-like receptor 4 inhibitor CLI-095 reduces the Interleukin-1β-elicited COX-2 protein expression, reactive oxygen species (ROS) production, vascular smooth muscle cells migration and endothelial dysfunction. Additionally, Interleukin-1β increases nuclear factor-erythroid 2-related factor 2 nuclear translocation and expression of its downstream proteins heme oxygenase-1, NAD(P)H:quinone oxidoreductase 1 and superoxide dismutase-2, by an oxidative stress-dependent mechanism; moreover, Interleukin-1β reduces the expression of the nuclear factor-erythroid 2-related factor 2 inhibitor Keap1. The nuclear factor-erythroid 2-related factor 2 activator tert-butylhydroquinone (tBHQ) reduces the effects of Interleukin-1β on the increased reactive oxygen species production and the expression of the proinflammatory markers (p-p38, p-JNK, p-c-Jun, COX-2), the increased cell proliferation and migration and prevents the Interleukin-1β-induced endothelial dysfunction in mice aortas. Additionally, tert-butylhydroquinone also reduces the increased MyD88 expression, NADPHoxidase activity and cell migration induced by lipopolysaccharide. Conclusions: In summary, this study reveals that Toll-like receptor 4 pathway contributes to the prooxidant and proinflammatory Interleukin-1β-induced effects. Moreover, activation of nuclear factor-erythroid 2-related factor 2 prevents the deleterious effects of Interleukin-1β, likely by reducing Toll-like receptor 4-dependent pathway. Although further research is needed, the results are promising as they suggest that nuclear factor-erythroid 2-related factor 2 activators might protect against the oxidative stress and inflammation characteristic of cardiovascular diseases.